Fuel for thought? South Africa's position on the multilateralisation of the nuclear fuel cycle. Issue 3 (2nd July 2016) - van Wyk, Jo-Ansie
ABSTRACT: The proponents of international nuclear fuel banks maintain that these banks will contribute to nuclear non-proliferation, whereas those opposing it maintain that nuclear weapon states support these banks in order to control and multilateralise the nuclear fuel cycle, thus preventing developing states from developing nuclear energy for peaceful purposes. Global inequalities pertaining to nuclear energy continue to persist despite developing states' efforts to reform the international nuclear energy regime. Moreover, some developing states maintain that these nuclear fuel banks perpetuate inequality in international relations. This is one of the reasons why some leading developing states, such as Brazil and South Africa, oppose these banks. South Africa, for example, intends to re-establish its nuclear fuel cycle and has declared uranium a strategic resource. Against the aforesaid, this article, following a constructivist approach, analyses the emergence and social construction of nuclear fuel banks as a practical expression of nuclear non-proliferation norms. The discussion also considers the inter-subjective understanding of these banks, as well as South Africa's opposition to them. The article concludes with an analysis of the implications of these opposing views for global equity, equality, nuclear non-proliferation and the peaceful uses of nuclear energy.